THE ROLE OF STATE REGULATION IN MODERN MARKET ECONOMY - V. Golubchikova (Вестник университета)
Highlighted the need and revealed the threat of the lack of state regulation of market economy. Considered the appointment, the key goals and objectives of state regulation in modern market economy of the Russian Federation. The characteristics of the functions and methods of state regulation of economy. The possibilities for activization of innovative development as one of the primary purposes of state regulation of the modern market economy.